Molecular Mechanisms Underlying Renin-Angiotensin-Aldosterone System Mediated Regulation of BK Channels - Zhang, Zhen-Ye; Qian, Ling-Ling; Wang, Ru-Xing (Frontiers in Physiology, 2017)
Large-conductance calcium-activated potassium channels (BK channels) belong to a family of Ca2+-sensitive and voltage-dependent potassium channels and play a vital role in various physiological activities in human body. The renin-angiotensin-aldosterone system is acknowledged as a vital body’s hormone system and plays a fundamental role in maintenance of water and electrolyte balance and blood pressure regulation. There is growing evidence that renin-angiotensin-aldosterone system has profound influences on the expression and bioactivity of BK channels. In this review, we focus on the molecular mechanisms underlying the regulation of BK channels mediated by renin-angiotensin-aldosterone system and its potential as a target for clinical drugs.